Ligand dynamics time scales identify the surface-ligandinteractions in thiocyanate-capped cadmium sulfide nanocrystals - Deshmukh, Samadhan H.; Chatterjee, Srijan; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2022)
The nanocrystal surface, which acts as an interface between thesemiconductor lattice and the capping ligands, plays a significant role in theattractive photophysical properties of semiconductor nanocrystals for use in awide range of applications. Replacing the long-chain organic ligands with shortinorganic variants improves the conductivity and carrier mobility of nanocrystal-based devices. However, our current understanding of the interactions betweenthe inorganic ligands and the nanocrystals is obscure due to the lack ofexperiments to directly probe the inorganic ligands. Herein, using two-dimensional infrared spectroscopy, we show that the variations in the inorganicligand dynamics within the heterogeneous nanocrystal ensemble can identifythe diversities in the inorganic ligand-nanocrystal interactions. The liganddynamics time scale in SCN-capped CdS nanocrystals identifies three distinctligand populations and provides molecular insight into the nanocrystal surface.Our results demonstrate that the SCN-ligands engage in a dynamic equilibriumand stabilize the nanocrystals by neutralizing the surface charges through both direct binding and electrostatic interaction.